Methodical features of physical rehabilitation of sportsmen with intra articulate injuries of ankle joint at the out-patient stage - Youssef Charbel; Denis Podkopai (Kharkiv State Academy of Physical Culture, 2016)
Purpose: the analysis of modern approaches to application of means and forms of physical rehabilitation of sportsmen with intra articulate injuries of ankle joint at the out-patient stage. Material & Methods: the analysis of urgent special references on the problem of treatment and rehabilitation at intra articulate injuries of ankle joint. Results: it is defined that together with the broad application of traditional complex techniques of medical physical culture, classical massage and physical therapy, the percent of use of nonconventional methods of non-drug therapy grows objectively and significantly in the last decade in physical rehabilitation. Conclusions: the connected application of east bath and special techniques of east massage for rehabilitation of sportsmen with intra articulate injuries of ankle joint at the out-patient stage in special literature is described not enough that in turn demands the additional practical researches among methods of non-drug therapy.